Análise das praças centrais da cidade de Rolândia - Paraná - Janesch, Zuleide Maria (2009)
The square is an urban space destined to all, this wants to say that it does not have distinction of who of it will make use. For this reason, when projecting it, the Public Power must hear who goes to use this space and to project it in order to also satisfy the yearnings of its users, becoming it accessible all. Taking as base this principle, was established as objective to evaluate the squares central offices of the city of Rolândia-PR, for the optics of its users, as well as identifying if the Public Power is being efficient in the treatment of its squares, mainly of the squares central offices, as for the necessities of its users. In this work one gave to emphasis to the thirteen squares central offices, remainders of the original plant of foundation occurred in 1934, of the City of Rolândia-PR. So that the main objective was reached, it was necessary to establish the specific objectives that if had translated the following actions: - to evaluate quantitatively and qualitatively the equipment, the furniture and the structures of the squares central offices; - to raise, quantitatively, the vegetation of the squares central offices; finally, - to hear the opinion of the Rolândia livers on the squares. The method developed for De Angelis that allows to raise, to register in cadastre, to diagnosis and to evaluate the public squares, from two approaches was used: the square while physical structure and the square seen for the population. This method allowed to answer to the objectives considered through the accomplishment of: a quali-quantitative survey of the equipment, structures and furniture; a quantitative survey of the existing vegetation in these public parks; e one questionnaire of opinion, carried through with the users of the squares central offices of the city of Rolândia- PR. One identified to the profile of the users of the squares central offices of the city of Rolândia-PR, arriving itself it the following constatations: that the users do not frequent the squares because they do not have time; the day where they costumed to go to the square is Saturday; the time of permanence in the squares has been of one hour; they go to the square to rest; what more squares like them that they frequent are to find friends and to talk; what they less like is of the policing lack. The gotten results had provided to arrive at the conclusion of that the squares central offices of Rolândia-PR are capable to offer quality of life to the citizens and contribute for the integration of the community, satisfying, thus, the necessities of its users. The level of acceptability of the squares central offices reached the percentage of 86,7%, however, the interviewed ones had requested improvements, that in its to understand, if make necessary, between them are to the question of the security guard. In this manner, the present study and its results they serve of subsidies to the Public Power for the actions of planning and management of these spaces destined to the population, a time that the same ones come from one questionnaire of opinion, where the proper population can be disclosed in relation to its squares.